2022
DOI: 10.1038/s41591-022-01705-6
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing antibodies against the SARS-CoV-2 Delta and Omicron variants following heterologous CoronaVac plus BNT162b2 booster vaccination

Abstract: This is a PDF file of a peer-reviewed paper that has been accepted for publication. Although unedited, the content has been subjected to preliminary formatting. Nature Medicine is providing this early version of the typeset paper as a service to our authors and readers. The text and figures will undergo copyediting and a proof review before the paper is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

46
314
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(360 citation statements)
references
References 21 publications
46
314
0
Order By: Relevance
“…Moreover, a heterologous booster dose can enhance more potent protection and neutralizing antibodies compared with a homologous booster dose [265]. This agrees with the results of Pérez-Then E, et al, who found that having a heterologous booster dose of BNT162b2 (Pfizer-BioNTech COVID-19 vaccine) for participants who had primary two doses of Sinovac vaccine, can cause increased neutralizing antibodies against Delta variant to be similar to those who received two doses of BNT162b2 vaccines and can increase the antibodies by 1.4-fold against Omicron variant compared to two doses of BNT162b2 vaccines [266].…”
Section: Is the Booster Dose Useful Or Not?supporting
confidence: 91%
“…Moreover, a heterologous booster dose can enhance more potent protection and neutralizing antibodies compared with a homologous booster dose [265]. This agrees with the results of Pérez-Then E, et al, who found that having a heterologous booster dose of BNT162b2 (Pfizer-BioNTech COVID-19 vaccine) for participants who had primary two doses of Sinovac vaccine, can cause increased neutralizing antibodies against Delta variant to be similar to those who received two doses of BNT162b2 vaccines and can increase the antibodies by 1.4-fold against Omicron variant compared to two doses of BNT162b2 vaccines [266].…”
Section: Is the Booster Dose Useful Or Not?supporting
confidence: 91%
“…The findings are suggestive of considerable heterogeneity in the magnitude and breadth of neutralization responses of Omicron in different groups ( Sievers et al, 2022 ). After 2 doses of Heterologous vaccination with CoronaVac vaccine there was no detectable Omicron neutralization but when boosted with BNT162b2, it showed 1.4 fold higher neutralization in comparison to 2 doses of mRNA vaccine ( Pérez-Then et al, 2022 ).…”
Section: Booster Shots Of Vaccinesmentioning
confidence: 99%
“…The heterologous boosting strategy refers to administering a vaccine that differs from the previous vaccine platform, potentially improving the immunogenicity and expanding the breadth of cellular and humoral immunity against current SARS-CoV-2 variants of concern (Barros-Martins et al, 2021;Munro et al, 2021). Heterologous boosting of CoronaVac with mRNA vaccine have shown not only induced the greater antibody response compared to other booster vaccine platform but also produced neutralizing antibodies against ancestral, Delta, and Omicron SARS-CoV-2 strain (Cheng et al, 2022;Costa Clemens et al, 2022;Perez-Then et al, 2022). The mRNA-1273 vaccine booster was administered 6 months after the second CoronaVac vaccination.…”
Section: Main Textmentioning
confidence: 99%